IMF Committee on Balance of Payments Statistics : Annual Report 1997. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 1998)
The IMF Committee on Balance of Payments Statistics was established in 1992 to promote accuracy and cooperation in the compilation of balance of payments statistics. Membership of the Committee, which advises the IMF on statistical issues, consists of representatives from a number of international organizations, central banks, and national statistical offices. The Committee's annual report for (Year) discusses recent trends in global balance of payment statistics and highlights the Committee's work program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Financial Markets; Investment Decisions; Portfolio Choice